The Comparative Study of Christian and Chinese Schools Operation During the Reign of King Prajadhipok - Chudasring, Ravee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
This research aims to study the operation and comparative study of Christian and Chinese schools’ operation during the reign of King Prajadhipok (King Rama VII). This qualitative research was conducted in accordance with analyzing the preliminary and secondary documents. The research found that during the reign of King Prajadhipok Christian schools and Chinese schools are successful in providing education. Especially in the language and profession Christian school can run well by reducing the role of missionaries in schools to open more opportunities for students. Despite the high tuition fees parents are confident to send more children to study. As well as building a reputation as a leading school and have a good relationship and is always trusted by government agencies. The Chinese school is trying to operate according to government policies. But the problem of not teaching Thai language and teaching political doctrines, especially nationalism and communism, which flows from the Chinese side became a problem that has been focused on the Siamese official. However, Christian schools and Chinese schools all have the same status, which is the private school and must be in the same regulatory standards. The government tries to balance the management in order not to look too lenient for Chinese schools and too strict for Christian schools.